I am stuck in deriving a specific formula concerning Lorentz-boosts. In my Classical Mechanics skript there is a chapter dealing with special relativity. In this chapter the Lorentz transformations are defined as being those linear transformations $\Lambda_\nu^\mu:{\mathbb R}^4 \rightarrow \mathbb R^4$, $x^\mu \rightarrow x'^\mu=\Lambda_\nu^\mu x^\nu+\rho^\mu$ that satisfy the equality $g_{\nu\mu}\Lambda_\sigma^\mu\Lambda_\rho^\nu=g_{\sigma\rho}$, where $g_{\nu\mu}$ is the metric tensor for flat space time.

Furthermore a specific transformation between two inertial systems O and O' is considered. This transformation relates the system O' and O if O' moves with velocity $\vec{v}$ relatively to O.
Then, for this specific situation, the formulas $\Lambda_0^0=\gamma$ and $\Lambda_0^i=\gamma \frac{v^i}{c}$ for $i=1,2,3$ are derived. (I appended the derivation in a picture below.)

Now to my question: My script states, that if the axis of both systems are paralell to each other it is also possible to derive formulas for the remaining components of $\Lambda_\nu^\mu$. These formulas are stated to be: $\Lambda_j^0=\gamma \frac{v^j}{c}$ and $\Lambda_j^i=\delta^i_j+\frac{v_iv_j}{\vec{v}^2}\gamma$. The proof for this equations is not carried out in the script but left as an exercis. I have tried really hard but was not able to do the derivation. I consider my problems to be rooted in my inability to figure out how to use the paralellity of the axes in the derivation. I would be really glad if someone could tell me how it is done correctly.

In the following you can find the derivation for $\Lambda_0^i$ and $\Lambda_0^0$ from my skript.

enter image description here


1 Answer 1


There is an error in your expression for the $\Lambda^i_{\;j}$ components. They actually read $$ \Lambda^i_{\;j} = \delta^i_j + (\gamma -1)\frac{v^i}{v}\frac{v_j}{v} = \delta^i_j + \frac{\gamma -1}{\beta^2}\frac{v^i}{c}\frac{v_j}{c} $$ with $\beta = v/c$, $v^2 = v^iv_i$.

Keeping this in mind, separate once again timelike and spacelike coordinates in the original transformation and use the already known components of $ \Lambda$: $$ dx'^0 = \Lambda^0_{\;0} \;dx^0 + \Lambda^0_{\;j} \;dx^j = dx^0 \left[ \gamma + \Lambda^0_{\;j} \frac{u^j}{c} \right]\\ dx'^i = \Lambda^i_{\;0} \;dx^0 + \Lambda^i_{\;j} \;dx^j = dx^0 \left[ \gamma\frac{v_i}{c} + \Lambda^i_{\;j} \frac{u^j}{c} \right] $$ where $ u^j/c = dx^j/dx^0$. Then take appropriate ratios to obtain the corresponding velocity transformations: $$ \frac{u'^i}{c} = \frac{\gamma\frac{v^i}{c} + \Lambda^i_{\;j} \frac{u^j}{c}}{\gamma + \Lambda^0_{\;j} \frac{u^j}{c}} $$ Consider now those displacements in the unprimed system that are along the direction of the relative velocity, such that $$ \frac{u^i}{c} = a\frac{v^i}{c},\;\;\;u^iu_i = ac^2 $$ for some $a\in \mathbb R$, and observe that the corresponding displacements in the primed system must also read $$ \frac{u'^i}{c} = a'\frac{v^i}{c},\;\;\;u'^iu'_i = a'c^2 $$ for some other $a'\in \mathbb R$. Substituting in the velocity transformations above yields a general relationship of the form $$ a'\frac{v^i}{c} = \frac{\gamma\frac{v^i}{c} + a \Lambda^i_{\;j} \frac{v^j}{c}}{\gamma + a \Lambda^0_{\;j}\frac{v^j}{c}}\;\;\;\;\;\;\;\;\;(1) $$ The information necessary to derive the $\Lambda$ components comes from the following particular cases:

  • From the isotropy of space it follows that $a=-1$ requires $a' = 0$, which can only happen provided $$ \Lambda^i_{\;j} \frac{v^j}{c} = \gamma\frac{v^i}{c}\;\;\;\;\;\;\;\;\;(2) $$

for any $v^i$.

  • The invariance of the speed of light further requires that for $a = \pm c/v\Leftrightarrow u^iu_i = c^2$, we must also have $a' = \pm c/v\Leftrightarrow u'^iu'_i = c^2$, and therefore $$ \pm \frac{c}{v}\frac{v^i}{c} = \frac{\gamma\frac{v_i}{c} \pm \frac{c}{v} \Lambda^i_{\;j} \frac{v^j}{c}}{\gamma \pm \frac{c}{v} \Lambda^0_{\;j}\frac{v^j}{c}} = \frac{\gamma\frac{v_i}{c} \pm \frac{c}{v} \gamma\frac{v^i}{c}}{\gamma \pm\frac{c}{v} \Lambda^0_{\;j}\frac{v^j}{c}} = \frac{\gamma(1 \pm \frac{c}{v} )}{\gamma \pm \frac{c}{v} \Lambda^0_{\;j}\frac{v^j}{c}}\frac{v^i}{c} $$ Solving for $ \Lambda^0_{\;j}\frac{v^j}{c}$ gives $$ \Lambda^0_{\;j}\frac{v^j}{c} = \gamma \frac{v_j}{c}\frac{v^j}{c}\\ \left[ \Lambda^0_{\;j} - \gamma \frac{v_j}{c}\right] \frac{v^j}{c} = 0 $$ and since the boost transformation is symmetric, we can conclude that $$ \Lambda^0_{\;j} = \gamma \frac{v_j}{c} $$

  • The above expressions for $ \Lambda^0_{\;j}$ simplify eq.(1) to $$ a'\frac{v^i}{c} = \frac{\gamma\frac{v^i}{c} + a \Lambda^i_{\;j} \frac{v^j}{c}}{\gamma\left(1 + a \frac{v^2}{c}\right)}\;\;\;\;\;\;\;\;\;(3) $$ and condition (2) further implies $$ a' = \frac{a+1}{1+a\frac{v^2}{c^2}} $$ However, eq.(3) can be rearranged eventually as $$ \left[ \Lambda^i_{\;j} - \left( \frac{1}{\gamma\left(1+a\frac{v^2}{c^2}\right)}\delta^i_{\;j} + \frac{\gamma(a+1)}{1+a\frac{v^2}{c^2}}\frac{v^i}{c}\frac{v_j}{c}\right)\right]\frac{v^j}{c} = 0 $$ which has to hold for any $a \in \mathbb R$. Since $\Lambda^i_{\;j}$ may depend only on the relative velocity, this means that it must be of the form $$ \Lambda^i_{\;j} = Q \delta^i_{\;j} + P \frac{v^i}{c}\frac{v_j}{c} $$ with $Q$ and $P$ some functions of the relative velocity such that $$ \left[ \left[ Q - \frac{1}{\gamma\left(1+a\frac{v^2}{c^2}\right)} \right] + \left[ P - \frac{\gamma(a+1)}{1+a\frac{v^2}{c^2}} \right] \frac{v^2}{c^2} \right] \frac{v^i}{c} = 0 $$ From this we have successively $$ Q + P \frac{v^2}{c^2} = \left[\frac{1}{\gamma\left(1+a\frac{v^2}{c^2}\right)} + \frac{\gamma(a+1)}{1+a\frac{v^2}{c^2}} \frac{v^2}{c^2}\right] = \gamma\\ P = \frac{\gamma - Q}{\beta^2}\\ \Lambda^i_{\;j} = Q \delta^i_{\;j} + \frac{\gamma - Q}{\beta^2} \frac{v^i}{c}\frac{v_j}{c} $$ The exact form of Q may now be determined from $g_{\mu\nu}\Lambda^\mu_\rho\Lambda^\nu_\sigma = g_{\rho\sigma}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.